Hematological, hepatic, and renal evaluation in Aotus azarai infulatus - Takeshita, R. S. C.; Monteiro, F. O. B.; Lins e Lins, F. L. de Miranda; da Silva, G. A.; Faturi, C.; Coutinho, L. N. [UNESP]; Monteiro, M. V. B.; Kugelmeier, T.; de Castro, P. H. G.; Muniz, J. A. P. C. (Wiley-Blackwell, 2011)
BackgroundKnowing the physiological ranges of certain hematological and biochemical parameters is necessary for understanding the alterations caused by pathogenic agents and establishing differences between states of health and disease. Hematological evaluations and clinical chemistry were performed on livers and kidneys from owl monkeys with different sexes and age ranges.MethodsForty-one healthy owl monkeys were evaluated (26 males and 15 females) in three different age groups (AG1 = 3 months to 1 year old; AG2 = 2-6 years old; AG3 = over 7 years old). The animals received physical exams, abdominal ultrasounds, and clinical laboratory tests.Results and conclusionsSignificant differences were observed in hematocrit and hemoglobin values between males and females. The levels of alkaline phosphatase in the tissues were significantly influenced by age. There was also a sex influence on blood urea nitrogen and creatinine levels. The results show that some hematological and clinical chemistry parameters in owl monkeys may be influenced by sex and age.
Keywords: Aotus; clinical enzymology; hemogram